CERAMICS ENCULTURATION OF ARTISANS’ COMMUNITY IN MAYONG LOR VILLAGE: ADAPTATION STRATEGIES IN THE PRESERVATION AND CONTINUATION OF LOCAL CULTURE CREATIVE POTENTIAL (Universitas Negeri Semarang, 2015)
The facts showed that traditional ceramic arts are one of the local cultural heritages in which their existence is not easily maintained and continued because of competition with modern industrial products in market. The opposite condition occurs in Mayong Lor village that this local cultural heritage is still well maintained and developed from generation to generation for about six centuries in communities. Thus, a fundamental question arises why and how this phenomenon occurs. This study examines ceramics enculturation problems of crafters in Mayong Lor village communities, Jepara as the manifestation of adaptation strategies in the preservation and continuation of local culture creative potential. Two approaches used as the basis of assessment strategies. First, the theoretical approach was applied through the approach of culture, aesthetics, structural functionalism, adaptation, and education. Next, the methodological approach was used through anthropological research approach operated by using qualitative research method. The results show that the ceramics enculturation of artisans’ in Mayong Lor village communities naturally appear to function as a cultural mechanism of ceramics traditional activities in the environment of crafter families. This cultural mechanism is the form of informal education as the manifestation of adaptation strategies in maintaining and continuing creative potential of ceramics culture in the community, across generations since 15th to 21th century. The local culture stakeholders are recommended to adopt or adapt the findings of this study as a model in determining policies for the development of conservation programs and local culture potential in their respective regions.